2013
DOI: 10.1186/1746-4269-9-78
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous and traditional plants: South African parents’ knowledge, perceptions and uses and their children’s sensory acceptance

Abstract: BackgroundThe dietary shift from indigenous and traditional plants (ITPs) to cash crops and exotic plant food sources increases the risk of malnutrition and other nutrition-related non-communicable diseases, especially in poor rural communities. Farm communities in South Africa have been associated with poor nutritional status and extreme poverty. ITPs have been found to be affordable sources of several micronutrients. However, knowledge of and the use of these plants are declining, and little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 22 publications
(38 reference statements)
4
27
0
Order By: Relevance
“…This study reveals that the main custodians of this knowledge are mostly mothers and traditional healers. This finding is in agreement of other authors [4,8,19]. Women who constituted 54% of the respondents were the most knowledgeable about plants used in disease management among children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study reveals that the main custodians of this knowledge are mostly mothers and traditional healers. This finding is in agreement of other authors [4,8,19]. Women who constituted 54% of the respondents were the most knowledgeable about plants used in disease management among children.…”
Section: Discussionsupporting
confidence: 92%
“…Traditional knowledge among the households is easily passed on orally to the young girls who are often care takers in these homes. This finding was in agreement with that of [19]. The girls are sent to go and pick these plants and also prepare the herbal medicine for the sick children.…”
Section: Discussionsupporting
confidence: 89%
“…Over millennia ago, in rural South African communities, indigenous and traditional crops were the main source of foods. However, with urbanisation there has been a shift from traditional foods to more western foods and these indigenous and traditional foods are less consumed [69]. The older generation have some knowledge of bambara groundnut [52], which was confirmed in the FGDs.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the mode of preparation, our results are in accordance with those of Manirakiza et al [50], in Congo-Kinshasa, who showed that the preparation of leafy vegetables such as spp., with peanuts and red palm oil occupy over half of the ingredients used. Van der Hoeven [51], in South Africa, showed that the ingredients used in preparation of vegetable dishes may vary and include oil, peanut butter, coconut, sodium bicarbonate, tomato and onion. Finally, Manduna & Vibrans [52], in Zimbambwe, the wild vegetables were cooked as spinach and served as a relish with the main staple, sadza.…”
Section: Mode Of Consumption Andmentioning
confidence: 99%